Modifikasi Perangkat Pembelajaran Kurikulum Merdeka untuk Anak Berkebutuhan Khusus di Jenjang PAUD - Amelia Rizky Idhartono; Nurul Hidayati; Arida Azka Nurina Ichwan; Sabrina Nur Fisabilillah (Universitas PGRI Adi Buana Surabaya, 2023)
Education is important for every human. Good education could bring great contribution and benefit in one quality improvement. Early education in PAUD, KB, and TK is the start of character building. Everyone have the right to have early education, including special needs children (ABK). Kurikulum merdeka has been implemented in teaching and learning process. The characteristic of kurikulum merdeka is suite the learning need of ABK that need flexibility in choosing learning tools, learning methods, learning strategy, learning media, and learning materials adjusted with competency and obstacles each special needs have. Teachers need to have deep understanding about those things so we can reach the purpose of special needs education. The education level in Indonesia starts from early childhood, family planning or kindergarten, elementary school, junior high school and high school. Education at the early childhood, family planning and kindergarten levels is the beginning of character building. At this level, it is also necessary to identify and early detect children with special needs. One of the efforts teachers can do to give the best educational service to ABK is to modified the learning tools of kurikulum merdeka in accordance with the needs and the capacity of each students. This efforts is needed so that each ABK could get suitable and good education. Partners in this PkM activity are PAUD, KB and TK teachers throughout Mojokerto. The problem faced by partners is the lack of understanding of learning tools in kurikulum merdeka for children with special needs at the level of PAUD, PG, and TK. This training and assistance was carried out online at gmeet which was held on June 3rd, 2023 from 14.00 to 17.00 WIB. In this PkM activity, the lecturers also involved 2 students from the Special Education Study Program. The conclusions of PkM activities are The conclusion of this PkM are: (1) The importance of deepening understanding about the needs and competencies of each special needs student; (2) The teacher must be able to decide which learning tools suite and fit each special needs student; (3) The importance the learning tools of kurikulum merdeka for ABK in PAUD level so that each student get the best education service that suite and fit their needs